2012
DOI: 10.5923/j.jce.20120201.03
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of TMT Rebar in Accelerated Corrosion

Abstract: Thermo-Mechanically-Treated (TMT) bars have recently been used as advancement over the conventional mild steel bars in reinforced concrete structures in order to enhance the durability in corrosive environment. Corrosion of steel reinforcement leads to cracking of reinforced concrete sections and thus may further reduce the load carrying capacity and serviceability of the structural members. Corrosion of rebars may cause reduction in yield strength of steel, affect the bond strength due to delamination of rust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…An important consequence of steel corrosion is the deterioration of its mechanical properties. Change in steel behavior can lead to unexpected problems and even to the undesired brittle failure due to a reduced cross section [2][3][4]. That is why it is of great importance to study the impact of corrosion on the mechanical properties in order to be able to make a correct assessment of the corroded steel structures.…”
Section: Introductionmentioning
confidence: 99%
“…An important consequence of steel corrosion is the deterioration of its mechanical properties. Change in steel behavior can lead to unexpected problems and even to the undesired brittle failure due to a reduced cross section [2][3][4]. That is why it is of great importance to study the impact of corrosion on the mechanical properties in order to be able to make a correct assessment of the corroded steel structures.…”
Section: Introductionmentioning
confidence: 99%
“…If the corrosion had been uniform along the bar, the adjusting trend lines would have been horizontal. However, the lines decrease for all loading speeds [21]. This is because corrosion is not homogeneous in the bar surface, but occurs in a series of pitting spots typical for chloride corrosion of steel [46,47].…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the loading speed, the ratio has a small fluctuation near a fixed value while the corrosion ratio changed from zero to more than 4%. It is indicated that the ratio of R m /R e is irrelevant to the average corrosion ratio which shows that the decrease of yield strength is induced by the decrease of effective cross-section area of the steel bars [9,21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many ways and standards for obtaining accelerated corrosion, which by its very nature is artificially caused. We will use a galvanostatic method, as do other researchers [2][3][4][5][6][7]. The acceleration of the corrosion process is accomplished by using an external source of direct current and anodic dissolution of the steel.…”
Section: Accelerated Corrosion Methods For Experimentsmentioning
confidence: 99%